UTILIZATION OF MICROBIAL ISOLATES FROM RHIZOSPHERE ZONES AS BIOFERTILIZERS TO ENHANCE GROWTH AND BIOCHEMICAL COMPONENTS IN THE PLANTS CYMOPSIS TETROGONOLOBA (CLUSTER BEANS) AND CAPSICUM ANNUM (CHILLY) - CHAIRMAN, K.; SINGH, A.J.A. RANJIT (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
The plants interact with physical, chemical and biological factors of soil system. Such systems are influenced by microorganisms and most of them are beneficial to plants and some may be pathogenic. In the rhizosphere region, certain groups of microorganisms are colonized. Some of these microbes are highly beneficial to plant as, they provide the nutrient. The present investigation indicated that the addition of microbes isolated from rhizosphere as bioinoculants to experimental crop had increased their growth significantly when compared to control. The efficacy of Rhizobium sp., Azotobacter sp., Azosprillium sp., present in the bioinoculam had increased the various growth parameters in Cynopsis tetrogonoloba and Capsicum annum. The plant height, shoot length, root length, leaf area, leaf size, internodal distance, chlorophyll a, b, protein content, nitrogen content and carotenoids content were increased due to the application of the bioinoculam developed.